ANALISIS KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA SMA PADA MATERI ARITMETIKA - Putri Cinndy Shylvia; Syihabuddin; Maulia Depriya Kembara (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Critical thinking ability is the ability of students when considering problems and deciding on a decision so as to solve a problem. The purpose of this study was to identify students' mathematical thinking skills on arithmetic material. This research used descriptive qualitative method. This research shows the results of student answers on arithmetic material related to students' mathematical critical thinking skills. The implementation of the research in class X in one of the private high schools in Bandung Regency, with a random sample selection of 40 students from class X.1 - X.5. This study used a question instrument including 4 description questions on arithmetic material. The analysis was carried out on student answers according to the question instrument indicators. The research results based on each indicator according to the percentage of critical thinking ability categories, it is known that 51% of students are able to interpret the problem, 50% of students can analyze and evaluate the problem, and 13% of students can evaluate inference or make conclusions correctly according to what is asked. Therefore, there are still many students who have low critical thinking skills